On fascistization: Mussolini's political project for Franco's Spain, 1937–1939. Issue 4 (8th August 2017) - Rodrigo, Javier
Abstract: 'Single party, single militia, single worker's union, on these three pillars the great Spain of tomorrow will be built', wrote Mussolini to Franco in August 1937, only four months after the new single party, Falange Española Tradicionalista y de las JONS, was created. From the Duce's point of view, all the political tools developed to achieve a brilliant present and a greater future were the result of Italian intervention in the Spanish Civil War. The political implementation of fascism, the single party, corporativism, propaganda and economic modernization were considered to have been derived from Italy's military and diplomatic involvement in Spain. But, surprisingly, that political presence has largely been undervalued by historians examining the political construction and nature of Franco's Spain. This article re-evaluates the importance, and limits, of Mussolini's political project in Spain: fascistization.